2012
DOI: 10.1063/1.4726243
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of binary FeSe superconducting wires by diffusion process

Abstract: (Abstract)We report successful fabrication of multi-and mono-core FeSe wires with high transport critical current density J c using a simple in-situ Fe-diffusion process based on the powder-in-tube (Fe-diffusion PIT) method. The seven-core wire showed transport J c of as high as 1027 A/cm 2 at 4.2 K. The superconducting transition temperature T c zero was observed at 10.5 K in the wire-samples, which is about 2 K higher than that of bulk FeSe. The Fe-diffusion PIT method is suitable for fabricating multi-core … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
45
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 21 publications
8
45
1
Order By: Relevance
“…Further, the low field J c values were also good as compared to the recently reported FeSe wire prepared by diffusion process [16]. The critical current densities of 350 A/cm 2 and 1,027 A/cm 2 were reported for FeSe tapes and several-core FeSe wires with Fe tapes, respectively [17]. The improved J c results can originate from a better grain connectivity due to the higher sintering temperature used in the present synthesis process.…”
supporting
confidence: 64%
“…Further, the low field J c values were also good as compared to the recently reported FeSe wire prepared by diffusion process [16]. The critical current densities of 350 A/cm 2 and 1,027 A/cm 2 were reported for FeSe tapes and several-core FeSe wires with Fe tapes, respectively [17]. The improved J c results can originate from a better grain connectivity due to the higher sintering temperature used in the present synthesis process.…”
supporting
confidence: 64%
“…Indeed, there are many reports about pressure-induced enhancement of T c in FeTe 0.5 Se 0.5 thin film [20][21][22] . Recently, we reported that the FeSe wires fabricated by the Fe-diffusion Power-in-tube PIT method showed T c zero ~10.5 K, about ~2 K above that of bulk sample 23 . This may come from a unique synthetic condition: FeSe wires were heat-treated at 800°C for 2 hours and taken out from a furnace to quench them.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a high transport Jc has not been achieved in the Fe-chalcogenide PIT wires (or tapes) with polycrystalline cores. The highest recorded transport Jc among the Fe-chalcogenide wires is about 1 kA/cm 2 under the self-field at 4.2 K in the FeSe wire fabricated by the in situ PIT method [14].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their high superconductivity performance at high magnetic fields, one of the potential applications of Fe-based superconductors is a superconducting wire or tape for magnets. Thus far, several types of Fe-based superconducting wires have been fabricated using A1-xKxFe2As2 (A = Ba, and Sr) [5][6][7][8], SmFeAsO1-xFx [9][10][11], and Fe chalcogenides (FeSe-based [12][13][14][15][16][17][18][19] or FeTe-based [20][21][22][23][24] superconductors). The FeAs-based superconducting wires (particularly, Ba1-xKxFe2As2 and Sr1-xKxFe2As2 wires) fabricated by the powder-in-tube (PIT) method showed a high critical current density (Jc).…”
Section: Introductionmentioning
confidence: 99%